Essentials of anatomy and physiology - Saladin, Kenneth S.; McFarland, Robin K. (New York : McGraw Hill Education, 2014)
This book is the newest product of a long collaboration between Ken Saladin and Robin McFarland. Robin was a contributor to the second edition of Ken's Human Anatomy text and provided valuable input over the years.
Part 1. Organization of the body -- Part 2. Support and movement -- Part 3. Internal Coordination -- Part 4. Circulation and defense -- Part 5. Intake and Output -- Part 6. Human life cycle.
Includes bibliographical references and index.
Keywords: HUMAN ANATOMY